When ESG Meets Foreign Capital: Market Valuation Evidence from Indonesia’s LQ45 - Adi Handika (Jurnal Ilmiah Wahana Akuntansi, 2026)
The relationship between Environmental, Social, and Governance performance and firm value remained theoretically contested in emerging capital markets, where investor heterogeneity and limited sustainability awareness complicated the valuation mechanism. This study examined whether Environmental, Social, and Governance risk exposure, as measured by the Sustainalytics Environmental, Social, and Governance Risk Score, where lower scores indicated better Environmental, Social, and Governance management, was significantly associated with firm valuation and whether foreign investor participation conditionally moderated this relationship among firms in the LQ45 index on the Indonesia Stock Exchange. Using an unbalanced panel of 73 LQ45 firms over 2020 to 2026 with 527 to 540 firm year observations, this study employed fixed effect panel regression with heteroskedasticity robust standard errors. An interaction model incorporating mean centred Environmental, Social, and Governance scores and net foreign investor flows was estimated, while logarithmic transformation was applied to address distributional skewness. The results showed that the Environmental, Social, and Governance Risk Score exhibited a positive and statistically significant effect on firm valuation at the 5 percent significance level. Higher scores, which denoted greater unmanaged Environmental, Social, and Governance risk, reflected the complex valuation dynamics of Indonesia’s resource intensive LQ45 composition. The interaction between Environmental, Social, and Governance Risk Score and foreign investor participation was also positive and highly significant, confirming that foreign investors amplified market sensitivity toward Environmental, Social, and Governance related information. These findings indicated that Environmental, Social, and Governance based market valuation in Indonesia was conditional rather than universal. Relevansi informasi Environmental, Social, and Governance terhadap valuasi perusahaan masih diperdebatkan di pasar modal negara berkembang. Penelitian ini menguji hubungan antara ESG Risk Score dan nilai perusahaan serta menilai apakah transaksi Net Foreign memoderasi hubungan tersebut pada perusahaan LQ45 di Bursa Efek Indonesia. Panel tidak seimbang mencakup 540 observasi perusahaan periode dari 73 konstituen dalam dua belas jendela observasi LQ45, mulai Februari sampai Juli 2020 hingga Agustus 2025 sampai Januari 2026, sedangkan regresi utama menggunakan 527 observasi dari 71 perusahaan. Model firm fixed effects utama menunjukkan koefisien ESG Risk Score dan interaksi ESG Risk Score × Net Foreign yang positif, tetapi koefisien langsung ESG menjadi tidak signifikan setelah efek waktu dimasukkan dan interaksi tertinggal tidak signifikan. Temuan menunjukkan bahwa penilaian risiko ESG bersifat kontemporer dan bergantung pada partisipasi perdagangan asing, periode pasar, dan lingkungan sektoral, bukan merupakan premi valuasi yang bersifat universal.